A method of chemiluminescence coupled with ultrafiltration for investigating the interaction between ibuprofen and human serum albumin. (18th December 2012) - Xiong, Xunyu; Zhang, Qunzheng; Nan, Yefei; Gu, Xuefan
ABSTRACT In acidic media, ibuprofen substantially enhanced the weak chemiluminescence (CL) produced by sodium sulfite and potassium permanganate. The increased signals were linearly correlated with ibuprofen concentrations ranging from 1.2 × 10‐3 to 4.8 μM, with a detection limit of 4.8 × 10‐4 μM. Two ultrafiltration (UF) membranes were used to construct a unit for trapping 0.15 and 0.75 μM human serum albumin (HSA) and coupled online with the CL system. At low HSA concentrations, the numbers of bound molecules per binding site were calculated to be 0.9 for Sudlow site I and 6.2 for Sudlow site II. The association constants on these binding sites were 5.9 × 105 and 3.4 × 104 M‐1, respectively. Our CL–UF protocol presents a rapid and sensitive method for studies on drug–protein interaction. Copyright © 2012 John Wiley & Sons, Ltd.